Seri Permai Training Resort / Mohd Saiful Azri Tan ... [et al.] - Tan, Mohd Saiful Azri; Yaacob, Mohammad Yari Suni; Alias, Nurul Izuan; Syed Said, Syarifah Salwa; Abu Bakar, Nur Azlina
Seri Permai Training Resort is a business that provides services training that our customers will be rejuvenated and ever ready to face the challenges ahead. We also provide Training Centre.Our outstanding facilities allow for a full range of training, bound meeting, company meetings, corporate family days, camps outs, corporate games, summer camp or just a holiday retreat to nature. Our training specialist are ready to assist you design and conduct your training requirement tailor - made to your corporate. image and budget. In introduction chapter, we give information about the shareholders background, partnership agreement and location of the business. It states the date of commencement, our business purpose and also the potential of our business. This business plan will explain in details about our business. Administration plan is very important in order to ensure that the administration is always in the best performance. Marketing plan is a planning of a promotion or other activity to attract customers in order to give information about our business. Target market and market analysis is create to identify the market for our business. Another planning is financial plan and operational plan. Financial plan is very important in running the business. Financial plan of Seri Permai Training Resort is prepared in order to ensure the cash flow of money is allocated. Financial plan give an overall view about business financial statement. Operational plan is also important because it is just like a basic planning of our business because our business provides · services to the customers. Operational plan will explain in detail to our customers about the operational activity that we done. That's why in this business, operational plan is very important. We choose to open this business because it has o good potentially to success now and more on the future. In conclusion, our business has a clear prospect to develop in the future.